High Performance (La, Sr)(Co, Fe)O3 Cathodes with Improved Adherence for Metal-Supported Fuel Cells. (30th May 2017) - Bram, Martin; Udomsilp, David; Roehrens, Daniel; Menzler, Norbert H.; Opitz, Alexander Karl; de Haart, L.G.J.; Guillon, Olivier
Abstract : A novel sintering approach was developed in order to overcome the issue of insufficient adherence of (La, Sr)(Co, Fe)O3 type cathodes in metal-supported solid oxide fuel cells (MSCs). Investigation of the phase stability of the perovskite structure at high temperature in various atmospheres with low oxygen partial pressures provided the basis for the development of a specific sintering procedure. After detailed investigation of the layer adherence, time dependent mechanical integrity and reversibility of phase transformations, metal-supported cells with cathodes sintered before cell operation (ex-situ sintering) could be produced reliably and were electrochemically characterized in single cell measurements. The novel sintering approach of such cathodes resulted in a significantly enhanced mechanical stability of the cathode layers. The adherence of the cathode to the electrolyte was considerably stronger, which is a substantial improvement in comparison with state-of-the-art MSCs. Furthermore, the electrochemical measurements revealed a beneficial effect regarding the cell performance.